Increased Circulating Cell-Free DNA in Eosinophilic Granulomatosis With Polyangiitis: Implications for Eosinophil Extracellular Traps and Immunothrombosis - Hashimoto, Teppei; Ueki, Shigeharu; Kamide, Yosuke; Miyabe, Yui; Fukuchi, Mineyo; Yokoyama, Yuichi; Furukawa, Tetsuya; Azuma, Naoto; Oka, Nobuyuki; Takeuchi, Hiroki; Kanno, Kyoko; Ishida-Yamamoto, Akemi; et al. (Frontiers in Immunology, 2022)
Background: Endogenous DNA derived from nuclei or mitochondria is released into the blood circulation as cell-free DNA (cfDNA) following cell damage or death. cfDNA is associated with various pathological conditions; however, its clinical significance in antineutrophil cytoplasmic antibody-associated vasculitis (AAV) remains unclear. This study aimed to evaluate the clinical significance of cfDNA in AAV. Methods: We enrolled 35 patients with AAV, including 10 with eosinophilic granulomatosis with polyangiitis (EGPA), 13 with microscopic polyangiitis, and 12 with granulomatosis with polyangiitis. Serum cf-nuclear DNA (cf-nDNA) and cf-mitochondrial DNA (cf-mtDNA) levels were measured by quantitative polymerase chain reaction before and after the initiation of immunosuppressive therapy. Tissue samples from EGPA patients were examined by immunofluorescence and transmission electron microscopy. The structure of eosinophil extracellular traps (EETs) and neutrophil extracellular traps (NETs) and stability against DNase were assessed in vitro. Platelet adhesion of EETs were also assessed. Results: Serum cf-nDNA and cf-mtDNA levels were significantly higher in AAV than in healthy controls, with the highest levels in EGPA; however, serum DNase activities were comparable among all groups. cf-nDNA and cf-mtDNA decreased after treatment and were associated with disease activity only in EGPA. Blood eosinophil count and plasma D-dimer levels were significantly correlated with cf-nDNA in EGPA and cf-mtDNA. EGPA tissue samples showed lytic eosinophils and EETs in small-vessel thrombi. The structure of EETs showed bolder net-like chromatin threads in vitro and EETs showed greater stability against DNase than NETs. EETs provided a scaffold for platelet adhesion. Conclusion: cfDNA was increased in EGPA, associated with disease activity. The presence of DNase-resistant EETs in small-vessel thrombi might contribute to higher concentration of cfDNA and the occurrence of immunothrombosis in EGPA.